Groupwork books published in Britain 1980-86 - Marchant, Harold (Groupwork, 2020)
The article reviews 13 books on groups and groupwork by European writers published in Britain during the years 1980-1986, It ranges from *self-help’ and growth-group approaches, through mainstream social groupwork, and applications to specialist settings. It provides a brief mime of the main concerns of each writer, and offers a lightly critical look at ‘homegrown groupwork literature’ during a particularly flourishing period. Publisher’s note: We are now putting all back issues of Groupwork on line. Articles in this issue have been scanned to pdf files as viable original typesetting files no longer exist. Though they may not look it, these files are searchable. This issue was published nearly 30 years ago. We have stated author professional details as received at time of publication.